Mapping the research on healthcare students' empathy: Insights from a bibliometric analysis - Hening Pratiwi; Susi Ari Kristina; Anna Wahyuni Widayanti; Yayi Suryo Prabandari (Pensoft Publishers, 2024)
Empathy is required not only by healthcare professionals but also by students as healthcare professionals' candidates. The research into the development of empathy in healthcare students is essential in the field of health education. This study aimed to investigate research trends in the topic of healthcare students' empathy using bibliometric analysis. We used the Scopus database on June 17, 2023, and "empathy" AND "students" AND "pharmacy" OR "medical" OR "dentist" OR "nurse" OR "nutritionist" are the search keywords. The remaining articles were examined using VOSviewer software. The results demonstrated a rapid increase in research on the topic of healthcare students' empathy between 2014 and 2023. The most prolific authors were Hojat, M., and Diaz-Narváez. The United States has the most publications and citations in this discipline. The keywords used in the current study were grouped into 7 clusters, and the term "human" is most frequently used. Our study contributes significantly to the developing literature on empathy for healthcare students.